Measuring what matters in healthcare: a practical guide to psychometric principles and instrument development - Swan, Katina; Speyer, Renee; Scharitzer, Martina; Farneti, Daniele; Brown, Ted; Woisard, Virginie; Cordier, Reinie (Frontiers in Psychology, 2023)
The provision of quality healthcare relies on scales and measures with robust evidence of their psychometric properties. Using measurement instruments with poor reliability, validity, or feasibility, or those that are not appropriate for the target diagnostic group or construct/dimension under consideration, may be unfavourable for patients, unproductive, and hinder empirical advancement. Resources from the COnsensus-based Standards for the selection of health status Measurement INstruments (COSMIN) group can assist in identifying and developing psychometrically sound measures. The COSMIN initiative is the only international, research-based practice taxonomy and methodological guidelines for measurement in healthcare. This manuscript aims to provide an accessible introduction to theories, principles and practices of psychometrics, instrument properties, and scale development, with applied examples from the COSMIN recommendations. It describes why measurement in healthcare is critical to good practice, explains the concepts of the latent variable and hypothetical construct and their importance in healthcare assessments, explores issues of flawed measurement and briefly explains key theories relevant to psychometrics. The paper also outlines a ten-step process to develop and validate a new measurement instrument, with examples drawn from a recently developed visuoperceptual measure for analysis of disordered swallowing to demonstrate key concepts and provides a guide for understanding properties of and terminology related to measurement instruments. This manuscript serves as a resource for healthcare clinicians, educators, and researchers who seek to develop and validate new measurement instruments or improve the properties of existing ones. It highlights the importance of using psychometrically sound measurement instruments to ensure high-quality healthcare assessments.